Complete chloroplast genome sequence of Chimonanthus praecox link (Calycanthaceae): an endemic plant species in China. Issue 3 (2nd July 2020) - Zhou, Guang-Can; Wang, Jie-Yu; Li, Wen; Zhang, Ming; Meng, Guo-Qing; Wang, Heng-Yi; Chen, Xiao; Wu, Yu-Han; Wu, Ping; Wang, Yi-Lei
Abstract: Chimonanthus praecox, a deciduous shrub tree, is endemic to China and widely cultivated in the world as a popular garden and ornamental plant. Here, we have reported its complete chloroplast genome with a length of 153, 181 bp, containing a large single copy (LSC) region of 86, 916 bp, a small single copy (SSC) region of 19, 767 bp and two identical inverted repeat regions (IRs) of 23, 249 bp. The overall GC contents of the plastome were 39.27%. A total of 114 unique genes were successfully annotated consisting of 80 protein-coding genes, 30 tRNA genes and four rRNA genes. Sixteen genes each possessed one intron and three genes had two introns. The ML phylogenetic analysis supports Chimonanthus as sister to Calycanthus . This result will be helpful for genetic breeding and population genetics of C. praecox, DNA barcoding of Chimonanthus, and phylogenetic studies of Calycanthaceae.